Patent Foramen Ovale Device Closure in Nepali Migrant Worker Performed at Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Chandra Mani; Safi, Sajjad; Timalsena, Birat krishna; Bogati , Amrit; Prajapati , Dipanker (Journal of National Heart and Lung Society Nepal, 2024)
Patent Foramen Ovale is highly prevalence in the general population and in patients with cryptogenic stroke. Patent Foramen Ovale device closure emerged as a practical solution to the problem of Patent Foramen Ovale-mediated illness. In patient with previous history of stroke and absence of other embolic etiologies with shunt across the Patent Foramen Ovale warrants closure. We highlight a Patent Foramen Ovale device closure of a migrant worker in Shahid Gangalal National Heart Centre.